ECONOMIC ASPECTS OF TERRORISM (With a Reference to the OSCE) - LINOTTE, Daniel (CENTRAL ASIA AND THE CAUCASUS, 2007)
This note addresses terrorism with a focus on selected economic and policy issues, including the actual role of the OSCE in the fight against terrorism. Considering the vast amount of literature on terrorism published after “9/11,” a selection of topics and reference material had to be made, partly relying on personal preferences and perception of the phenomenon. However, we believe that the selected issues are relevant for addressing terrorism from the standpoint of economic policy at least.Four parts are distinguished: —The first one reviews a set of preliminary issues such as defining terrorism, history, geography, data and research. —The second part presents recent findings about the costs of terrorism and the benefits of antiterrorism.—The third part concentrates on the economic analysis of the phenomenon and policy implications: statistical regularities and forecasting, poverty, suicide terrorism, wealth and sponsoring, and immigration.—The fourth part summarizes the role of the OSCE economic dimension in the fight against terrorism.It should be made clear that terrorism is a very complex phenomenon that combines many factors such as ethnicity, minority/majority status and relations, social stratification and mobility, “territoriality” and statehood, etc. Subsequently, for the sake of effectiveness and success, economic policy measures that address terrorism must be designed in the context of broader policies and strategies that integrate other, and possibly, more important dimensions, including the need for a sustainable peace settlement in the Middle East, and moving ahead with democratization and the protection of human rights in many countries, including those that are seen as “fragile states” by the OECD.